2019
DOI: 10.3389/fnins.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Common miRNA Patterns of Alzheimer’s Disease and Parkinson’s Disease and Their Putative Impact on Commensal Gut Microbiota

Abstract: With the rise of Next-Generation-Sequencing (NGS) methods, Micro-RNAs (miRNAs) have achieved an important position in the research landscape and have been found to present valuable diagnostic tools in various diseases such as multiple sclerosis or lung cancer. There is also emerging evidence that miRNAs play an important role in the pathogenesis of neurodegenerative diseases such as Alzheimer’s disease (AD) or Parkinson’s disease (PD). Apparently, these diseases come along with changes in miRNA expression patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…For instance, in a cross-sectional study, AD patients had an exacerbated nutritional status compared to age-matched controls (Saragat et al, 2012). An alternative mechanism of how the host affects microbiota in the context of AD has been hypothesized by us in a recent in silico study (Hewel et al, 2019). In this previous work, we demonstrated that host miRNAs differentially expressed in patients suffering from AD have the potential to bind on key regulatory sequences in commensal microbiota, thereby possibly regulating transcription in bacterial pathways.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, in a cross-sectional study, AD patients had an exacerbated nutritional status compared to age-matched controls (Saragat et al, 2012). An alternative mechanism of how the host affects microbiota in the context of AD has been hypothesized by us in a recent in silico study (Hewel et al, 2019). In this previous work, we demonstrated that host miRNAs differentially expressed in patients suffering from AD have the potential to bind on key regulatory sequences in commensal microbiota, thereby possibly regulating transcription in bacterial pathways.…”
Section: Discussionmentioning
confidence: 74%
“…In accordance with the literature, we found high levels of circulating LPS in patients with ND [34,35] with a significant correlation between LPS and Nox2. A recent study identified micro-RNA binding sites related to gut bacteroidetes and proteobacteria that could explain the mechanism of lipopolysaccharide biosynthesis in AD and PD [36]; however, the mechanism of LPS increase deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miRNA produced by intestinal epithelial cells can enter bacteria and regulate gene transcription and growth [74]. The fecal miRNA patterns in PD patients have been shown to differ from healthy controls [75]. Bacterial lipopolysaccharide, in turn, has been shown to alter miRNA expression in macrophages leading to a cascade of inflammatory responses [76].…”
Section: Introductionmentioning
confidence: 99%